Influence Standardization ISO 9001: 2008 and Culture Organization on Employee Performance at PT. Sumberdaya Dian Mandiri - Laras Dwi Hartini; Noor Indah Rahmawati (Inspire Global Insight Journal, 2026)
Lack of employee awareness regarding the importance of ISO standardization, especially ISO 9001:2008 as a supporter of company quality, the lack of effectiveness in implementing ISO 9001:2008 standardization, employee performance is not optimal by not coming in according to working hours so that work is not completed on time time Which has determined become problem in process achievement objective company. This study aims to determine how much influence ISO 9001: 2008 standardization has on employee performance, the influence of organizational culture on employee performance and the influence of ISO 9001: 2008 standardization and organizational culture on employee performance simultaneously. Analysis The data in this study used the SPSS version 17 method to determine the relationship between variables, using multiple regression and correlation analysis as well as hypothesis testing using the t test and F test. This study shows a positive influence between ISO 9001: 2008 standardization (X1) on employee performance. (Y) with Thitung 3,056 > Table 1,989 And mark probability 0.003. Whereas For variable (X2) culture organization to performance employee (Y) results Which obtained -1,241 <from 1,989 with The probability value of 0.218 means that there is no influence between the variable (X2) of organizational culture on employee performance (Y). For the results of the hypothesis using the f test, the results obtained are that employee performance is influenced by ISO 9001:2008 standardization and organizational culture simultaneously by 10.9%. Hypothesis testing shows the influence of ISO 9001:2008 standardization and organizational culture simultaneously on employee performance. By Because That, For increase performance employee, company need stage training ISO 9001: 2008 in a way evenly to all employee so that understanding employee more wide about The importance of ISO 9001: 2008 standardization, the implementation of organizational culture is increasingly being improved to truly be absorbed and employees are willing to understand the meaning of the organizational culture itself.